2022
DOI: 10.1002/adfm.202112837
|View full text |Cite
|
Sign up to set email alerts
|

Polydimethylsiloxane‐Silane Synergy enables Dropwise Condensation of Low Surface Tension Liquids

Abstract: Despite decades of research on promoting the dropwise condensation of steam, achieving dropwise condensation of low surface tension liquids remains a challenge. The few coatings reported to promote dropwise condensation of low surface tension liquids either require complex fabrication methods, are substrate dependent or have poor scalability. Here, the rational development of a coating, which is applicable to all conventionally used condenser metals, is presented by combining a low contact angle hysteresis pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Very few surface modification techniques have succeeded in achieving scalable and sustainable dropwise condensation of low surface tension liquids. 234–236 Studies on lubricant infused structured surfaces (LIS) have introduced the methodology of modifying micro and nanostructured surfaces with lubricant infusion for enabling enhanced condensation of liquids. 230,237–239 Lubricant infused nanostructured surfaces have successfully been implemented to achieve stable dropwise condensation of toluene, ethanol, hexane, and pentane which are low surface tension fluids (Fig.…”
Section: Condensationmentioning
confidence: 99%
“…Very few surface modification techniques have succeeded in achieving scalable and sustainable dropwise condensation of low surface tension liquids. 234–236 Studies on lubricant infused structured surfaces (LIS) have introduced the methodology of modifying micro and nanostructured surfaces with lubricant infusion for enabling enhanced condensation of liquids. 230,237–239 Lubricant infused nanostructured surfaces have successfully been implemented to achieve stable dropwise condensation of toluene, ethanol, hexane, and pentane which are low surface tension fluids (Fig.…”
Section: Condensationmentioning
confidence: 99%
“…In recent work, researchers have prepared a siloxane‐silane coated surface using chemical vapor deposition (CVD) to enhance the dropwise condensation of low‐surface‐tension liquids. [ 44 ] Although the coating successfully reduced the contact angle hysteresis and enabled dropwise condensation, the surfaces remained oleophilic (contact angles well below 90°). To fabricate surfaces that can successfully repel low‐surface‐tension liquids, researchers have shown that specially designed re‐entrant structures are required to prevent the liquid from spreading.…”
Section: Introductionmentioning
confidence: 99%
“…It can lead to a significantly high thermal resistance of more than 10 –5 m 2 ·K·W – 1 on a copper substrate, compromising the heat transfer benefits from the dropwise condensation mode. To reduce the thermal resistance, ultrathin polymer brushes (ideally at the nanoscale level), such as polydimethylsiloxane (PDMS) brushes, can be grafted onto the metal substrate. The coatings are ultrathin (∼6 nm) with low thermal resistance (<10 –7 m 2 ·K·W – 1 , Figure S1, Supporting Information) and able to repel water drops with low contact angle hysteresis (<10°).…”
Section: Introductionmentioning
confidence: 99%